A UK survey of the experience of service provision for children and young people with epilepsy. (August 2018) - Williams, Fiona; McCafferty, Aileen; Dunkley, Colin; Kirkpatrick, Martin
Highlights: A UK survey obtained over 2300 responses from parents and young people about their experience of their epilepsy service. The most powerful factor affecting satisfaction related to how easy it was to contact the epilepsy service. This has important implications for service design and provision. Multi-level regression modelling is a useful tool to identify the most powerful factors determining patient satisfaction. Abstract: Purpose: To survey patient and carer experience for children and young people with epilepsy across the United Kingdom. Methods: We used a Patient Reported Experience Measure methodology to explore perceived satisfaction with their epilepsy service. A survey collected anonymised proxy data on demography and illness severity, and perceptions of interaction with clinicians, ease of access to the service and the quality and quantity of epilepsy information provided. The questionnaire was completed by the child's or young person's carer or by the young person. Results: Survey questionnaires were distributed across all of the 192 paediatric units providing epilepsy care for children in the UK. 145 units (75%) submitted data and there were 2335 responses. 90% of young people and 86% of carers were satisfied with the care they had received. Using multi-level logistic regression modelling, those factors most strongly affecting satisfaction were determined. While many proxies of illness severity adversely affected satisfaction, comorbidity did not. A dedicated clinic setting, perceived adequate information and guidance on restrictions on their child, if any, all improved satisfaction. However, the significantly strongest factor influencing satisfaction was "ease of access" to the service. Conclusions: These data demonstrate the feasibility of collecting large population sizes to allow a better understanding of the needs of children and young people accessing an epilepsy service. They allow the identification of factors most closely linked to patient satisfaction and provide potentially valuable information on how to improve the quality of care of children and young people with epilepsy.